The texture of non-fat yogurt with proteins isolates and concentrates - I. A. Gurskiy (Пищевые системы)
Yogurt is one of the most common fermented milk products. It is consumed directly as food or used for the production of fermented milk desserts and ice cream. The urgent task for yogurt producers is improving product quality due to additionally introduced protein components. In this study, an effect of protein isolates and concentrates on the rheological parameters of yogurt was evaluated. The methods included the determination of dynamic viscosity and texture indices, such as hardness, gumminess, chewiness, springiness, cohesiveness and adhesiveness. The prepared yogurt samples were investigated immediately and after 30 days of storage at a temperature of 4±2°C. The water-holding capacity was evaluated. It has been established that introduction of whey proteins makes it possible to increase the water-holding capacity to 77% and 80%, respectively. The highest value of dynamic viscosity (19.3 and 26.1 Pa·s) was found in the samples with isolate and concentrate of native whey proteins after 5 hours of fermentation. A decrease in dynamic viscosity with the introduction of milk protein isolate, soy protein concentrate and native whey protein isolate was observed after 5 hours of fermentation. Addition of the protein components led to a significant increase in texture indices, except for cohesiveness. The highest cohesiveness value of 0.4 N·s was found in the sample without protein components and in the sample with whey protein concentrate. The indicators of hardness, gumminess, chewiness, springiness and adhesiveness were the highest in the sample with native whey protein isolate.